0050 The Role of Poverty and Perceived Stress on Insomnia Symptom Severity During the COVID-19 Pandemic. (25th May 2022) - Egeler, Mara; Hire, Veronica; Walker, Jamie; Vargas, Ivan
Abstract: Introduction: In 2020, poverty in the United States increased as the COVID-19 pandemic led to the loss of work and/or income. Recent research has also shown that stress caused by the pandemic has led to increased rates of poor sleep. While insomnia rates have increased nationwide, it is not yet known if those living in poverty experienced insomnia symptoms at disproportionate rates. This study examined the effect poverty has had on insomnia symptom severity, as well as whether perceived stress mediated this association. Methods: Survey data was collected from 3, 775 U.S. adults (83.1% White, 78.6% female, age = 18 – 86 years old) during the initial months of the COVID-19 pandemic (April-June 2020). These data were used for a secondary analysis. Participants completed an online survey aimed to assess basic demographics, sleep, physical activity, social engagement, and overall stress levels. Poverty was defined using the poverty guidelines provided by the Department of Health and Human Services (i.e., based on self-reported income and family/household size). The Insomnia Severity Index (ISI) was used to assess insomnia symptoms. Perceived stress was assessed using the Perceived Stress Scale (PSS). Results: 316 participants (8.4%) met criteria to be considered living below the poverty threshold. Those below the poverty threshold had a mean ISI of 10.20 (95% CI: 9.54, 10.86), while those above the poverty threshold had a mean ISI of 8.33 (95% CI: 8.13, 8.53). Put differently, 26.6% of those below the poverty threshold met criteria for clinical insomnia (i.e., ISI > 14), whereas 15.9% of those above the poverty threshold met criteria for clinical insomnia. Finally, a mediation test (with bootstrapping) confirmed that the association between poverty and insomnia was partially mediated by perceived stress (indirect effect = 1.15, 95% CI: 0.76, 1.55). Conclusion: While poverty guidelines vary by state, these data generally support that there are notable disparities in sleep and insomnia based on family/household income, and that these differences are, in part, due to greater perceived stress. This may be due to increased stress related to loss of work or income. Future studies examining the impact of pandemic stress on insomnia should consider the role of socio-economic status. Support (If Any): K23HL141581 (PI: Vargas); R25HL10544 (PI: Jean-Louis); K24AG055602 (PI: Perlis)